Innovation in Bag Products Using Scrap Fabric and Quilting Techniques - Arrsyi, Esty Nurbaity; Maulida, Ernita; Triwulandari, Defani (VISIORA: Journal of Creative Industries and Vocational Innovation, 2025)
This study aims to obtain the results of bag product innovation with patchwork using quilting techniques assessed by 5 expert panelists based on product innovation theory (Kotler et al., 2015) including indicators of product quality, product features, and product style and design and based on the theory of design elements (Wilson & Textile Institute (Manchester, 2001) including size, color, texture, and line. The research method used quantitative with pre-experimental design, one-shot case study. The waist bag products made are in the form of 5 designs with different designs and colors. The data collection technique used a mixed questionnaire. The overall product innovation results based on indicators of product quality, product features, product style and design, and application of design elements obtained a score of 85.2 in the very good category. Product innovation theory includes product quality indicators consisting of quality level and quality consistency getting very good scores. Product feature indicators get very good scores. and Product style and design indicators consisting of increasing competitive advantage and form factor get very good scores. The theory of design elements consisting of size indicators, color indicators, texture indicators, and line indicators get very good scores. The product with the highest assessment is obtained by design 3 and the lowest value is obtained by design 1 with a very good category among the five product designs.